2009
DOI: 10.1515/comm.2009.010
|View full text |Cite
|
Sign up to set email alerts
|

News for adolescents: Mission impossible? An evaluation of Flemish television news aimed at teenagers

Abstract: Media companies as well as governments launch initiatives to reverse the decline in news consumption by adolescents. Since 2007, the Flemish government has been funding newscasts for adolescents on two commercial channels, Zoom on VTM and Jam on VT4. In 2008, these programs were evaluated using in-depth interviews with producers, content analysis of 30 episodes of each program, an analysis of the ratings for the first season, and an online survey among 663 adolescents aged 10 to 18. Results indicate that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It showed that in particular young viewers enjoy arousing news stories. Recent developments in the news market, such as the emergence of highly arousing newscasts that especially aim at younger viewers (Vandebosch, Dhoest, and van den Bulck, 2009), seem beneficial to attract this viewer category. However, news producers should be cautious.…”
Section: Discussionmentioning
confidence: 99%
“…It showed that in particular young viewers enjoy arousing news stories. Recent developments in the news market, such as the emergence of highly arousing newscasts that especially aim at younger viewers (Vandebosch, Dhoest, and van den Bulck, 2009), seem beneficial to attract this viewer category. However, news producers should be cautious.…”
Section: Discussionmentioning
confidence: 99%
“…To attract young viewers, news is packaged in a flashy, attractive, and contemporary fashion that is stylistically different from the adult news (cf. NOS, 2007; Vandebosch et al, 2009).…”
Section: Age-related Preferences For Negative Content and Tabloid Packagingmentioning
confidence: 99%
“…To attract young viewers, news is packaged in a flashy, attractive, and contemporary fashion that is stylistically different from the adult news (cf. NOS, 2007;Vandebosch et al, 2009). Theoretical support for these news programs' strategies is offered by the activation model of information exposure (Donohew, Lorch, & Palmgreen, 1998;Donohew, Palmgreen, & Duncan, 1980) and, in particular, by those elements of the model that are based on Zuckerman's sensation-seeking theory (Zuckerman, 1994).…”
Section: Age-related Preferences For Negative Content and Tabloid Pacmentioning
confidence: 99%
See 2 more Smart Citations